Exchange rates and fundamentals - Charles Engel; Kenneth D. West (European Central Bank (ECB), 2003)
Standard economic models hold that exchange rates are influenced by fundamental variables such as relative money supplies, outputs, inflation rates and interest rates. Nonetheless, it has been well documented that such variables little help predict changes in floating exchange rates – that is, exchange rates follow a random walk. We show that the data do exhibit a related link suggested by standard models that the exchange rate helps predict fundamentals. We also show analytically that in a rational expectations present value model, an asset price manifests near random walk behavior if fundamentals are I(1) and the factor for discounting future fundamentals is near one. We suggest that this may apply to exchange rates.
Keywords: F31; F37; G15; G12; 330; asset price; Exchange Rates; monetary model; present value; random walk